2021
DOI: 10.31018/jans.v13i3.2795
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil exchangeable nutrients across different land uses in steep slopes of Mizoram, North-east India

Abstract: Land use change resulting from anthropogenic pressure on land has led to degraded soil quality, especially in the hilly tropical regions where ecosystems are generally fragile and susceptible to soil degradation from cultivation. Hence, sustainable land uses and management practices are crucial for agricultural production and ecological balance, particularly in these regions. The present study investigates the impact of various hill land uses (Natural forest-NAF, Jhum fallow-JF, Home garden-HG, Acacia pennata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The pH for both disturbed and undisturbed were low (5.06-5.53, Table 1 and Table 2 ) therefore the soil is acidic in nature. The pH readings are in line with similar studies (11)(12)(13) . The upper depth of undisturbed forest is more acidic (5.06) than the lower depth (5.53), this can be attributed to leaching of nutrients due to high precipitation in the study area.…”
Section: Resultssupporting
confidence: 91%
“…The pH for both disturbed and undisturbed were low (5.06-5.53, Table 1 and Table 2 ) therefore the soil is acidic in nature. The pH readings are in line with similar studies (11)(12)(13) . The upper depth of undisturbed forest is more acidic (5.06) than the lower depth (5.53), this can be attributed to leaching of nutrients due to high precipitation in the study area.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies also reported greater CEC for home garden soils of southern Ethiopia (Wolka et al, 2021), but also in Uganda and Kenya (Tittonell et al, 2013) and on the east coast of Peninsular, Malaysia (Yusoff et al, 2017). Similarly, the continuous addition of manure, compost, and ash to the soils around the homesteads contributed to greater P (>20 ppm), (Miheretu and Yimer, 2018) and K values (Ovung et al, 2021;Dori et al, 2022).…”
Section: Tablementioning
confidence: 75%